Critical Trauma Studies : Understanding Violence, Conflict and Memory in Everyday Life - Wertheimer, Eric H.R; Casper, Monica J., 1966- (Book collections on Project MUSE., 2016)
Trauma is a universal human experience. While each person responds differently to trauma, its presence in our lives nonetheless marks a continual thread through human history and prehistory. In Critical Trauma Studies, a diverse group of writers, activists, and scholars of sociology, anthropology, literature, and cultural studies reflects on the study of trauma and how multidisciplinary approaches lend richness and a sense of deeper understanding to this burgeoning field of inquiry. The original essays within this collection cover topics such as female suicide bombers from the Chechen Republic, singing prisoners in Iranian prison camps, sexual assault and survivor advocacy, and families facing the devastation of Hurricane Katrina. As it proceeds, Critical Trauma Studies never loses sight of the way those who study trauma as an academic field, and those who experience, narrate, and remediate trauma as a personal and embodied event, inform one another. Theoretically adventurous and deeply particular, this book aims to advance trauma studies as a discipline that transcends intellectual boundaries, to be mapped but also to be unmoored from conceptual and practical imperatives. Remaining embedded in lived experiences and material realities, Critical Trauma Studies frames the field as both richly unbounded and yet clearly defined, historical, and evidence-based.